2016
DOI: 10.4014/jmb.1512.12070
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy for Thermostability Improvement of Trypsin Based on N-Glycosylation within the ��-Loop Region

Abstract: The Ω-loop is a nonregular and flexible structure that plays an important role in molecular recognition, protein folding, and thermostability. In the present study, molecular dynamics simulation was carried out to assess the molecular stability and flexibility profile of the porcine trypsin structures. Two Ω-Loops (fragment 57-67 and fragment 78-91) were confirmed to represent the flexible region. Subsequently, glycosylation site-directed mutations (A73S, N84S, and R104S) were introduced within the Ω-loop regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Enhanced thermal stability is generally an essential requirement for those enzymes that are used as biocatalysts in industrial processes occurring at high temperatures. To this end, an enzyme can be modified by enhancing glycosylation 46 , 47 , or by introducing disulfide bridges 48 , salt-bridges 49 , or hydrogen bonds 50 . In particular, the introduction of disulfide bonds provide considerable stability to proteins by locking their fold in a well-defined local or global conformation 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced thermal stability is generally an essential requirement for those enzymes that are used as biocatalysts in industrial processes occurring at high temperatures. To this end, an enzyme can be modified by enhancing glycosylation 46 , 47 , or by introducing disulfide bridges 48 , salt-bridges 49 , or hydrogen bonds 50 . In particular, the introduction of disulfide bonds provide considerable stability to proteins by locking their fold in a well-defined local or global conformation 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the resistance of phytase to high temperature is a necessary property. To improve its thermal resistance, an enzyme could be modified by enhancing glycosylation [16,44,47], or adding disulfide bridge [35,38], salt-bridges [21,49], or hydrogen bonds [44,45,49,50], as well as other rational design strategies [3,41,46]. Directed evolution of enzymes is also utilized [22,36,37,51].…”
mentioning
confidence: 99%
“…In recent years, a number of effective approaches, such as enzyme immobilization, protein engineering, and use of cosolvents, have been successfully utilized to improve the thermostability of trypsin [ 5 7 ]. For example, Pazhang et al reported that polyols (sorbitol and glycerol) stabilized trypsin by decreasing the polypeptide chain fluctuations.…”
Section: Introductionmentioning
confidence: 99%